Retos y oportunidades de la ampliación de la Unión Europea para México y América Latina - Ruano, Lorena (Revista Mexicana de Política Exterior, 2022)
The author explains how the enlargement of the European Union presents a series of challenges and opportunities for Mexico and Latin America in economic and political terms, and in the area of cooperation for development. Economically speaking, Mexico will have the advantage of access to the markets of the 10 new Member States, due to the free trade agreement it has entered into with the European Union. However, Ruano believes trade and investment will be redirected, and that this will make new Member States in Southern and Eastern Europe more attractive. As regards cooperation, enlargement will begin to take its toll on the European Union’s budget after 2006, and, consequently, it is highly likely that we will see a reduction in the resources that are currently earmarked for development. Finally, the author believes that the most transcendental effects will be in the political and diplomatic arenas; ties with a series of States will be strengthened, but Mexico and Latin America will undoubtedly find themselves facing a new European Union more prone to introspection, with greater geo-strategic and diplomatic weight, and a more decisive, but more difficult role to fulfill.